Transforming Democratic Policing in the Digital Era for Law Enforcement Accountability in Indonesia - Idris Sandiya; A. Hanief Saha Ghafur; Solikhah Yuliatiningtyas (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2025)
The phenomenon of “No Viral No Justice” illustrates how legal justice is increasingly shaped by social media exposure, where only viral cases tend to receive serious attention from law enforcement agencies. This article analyzes the relationship between social media virality and the concept of Democratic Policing (DP), introducing a new conceptual framework termed Digital Democratic Policing (DDP). Through a literature review of 18 scientific journal articles, this study integrates five primary theories: (1) Social Movement Theory, (2) Public Sentiment Analysis, (3) Media Exposure Theory, (4) A Theory of Justice, and (5) Democratic Policing. The findings indicate that digitalization has enhanced DP practices by making them more transparent, participatory, and open to public scrutiny. However, digitalization also creates challenges, including trial by social media and the spread of disinformation. Within this context, the DDP framework is positioned not only as a response to the digital era but also as a medium for legal reform, emphasizing technology-based transparency, public participation in digital spaces, and accountable police governance. By embedding DDP into broader law enforcement reforms, policing can move beyond reactive measures toward a proactive system that restores legal certainty and strengthens democratic legitimacy. This study expands the scope of DP research into the digital domain and recommends adaptive policing policies grounded in justice, democracy, and reform-oriented practices. Generally, the DP approach shifts law enforcement from a coercive model to one that is collaborative and responsive, where legal legitimacy is primarily built upon public trust, forming the core of democratic security systems.